Edukasi Optimalisasi 1000 Hari Pertama Kehidupan Sebagai Upaya Menurunkan Angka Kematian Ibu - Mergy Gayatri; Sutrisno Sutrisno; Bambang Rahardjo; Krisjentha Iffah Agustasari; Dian Kusumaningtyas; Ratna Diana Fransiska; Kentri Anggarina Gumanti; Oluwadamilare Akingbade (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
One of the strategies to improve the mothers' well-being of mothers and new-borns is optimizing the first 1000 days after birth starting from preparation for pregnancy. By optimizing pregnancy preparation, mothers are expected to have a healthy pregnancy which will affect the outcome of their pregnancy. The community service aimed to educate the public, including health care staff in Indonesia as main providers of maternal health in order to assist mothers and their partners in preparing for their pregnancy. The output of this community service is the knowledge transfer about pregnancy preparation and pregnancy period in order to optimize the First 1000 Days. The results showed that the majority of participants consisted of midwives, indicating that midwives were still enthusiastic about enhancing their knowledge regarding pregnancy. The evaluation showed that the majority of participants were satisfied with the topic provided. Similar community service is recommended to be implemented in a small scale of community group in order to have an intensive education.